Constructing Substitute Social Interaction Design: A System to Alleviate Social Anxiety Disorder through Library Interactions - Teng-Wen Chang; Hsin-Yi Huang; Hsiang-Ting Chien; Shih-Ting Tsai (Journal of Library and Information Studies)
As libraries evolve into dynamic social spaces, they present new opportunities for alternative social interactions. This study explores how books can serve as a medium to foster connections, particularly among individuals with social anxiety disorder (SAD). We propose a “library-based social network” built on two key data points: (1) book reviews and (2) records of who has read or intends to read a book. Instead of asking, “Who else likes this book?” we shift the focus to “Who would be delighted to discover this hidden book?”—encouraging social engagement through shared literary experiences. Individuals with SAD often find traditional social media overwhelming. Inspired by architect Rem Koolhaas’s vision of adaptable public spaces, we examine how libraries can function as spaces for bibliotherapy, where reading provides comfort and indirect social connection. Our methodology combines contextual analysis and user interviews to align library interactions with user behaviors and preferences. Our findings suggest that interactive book-sharing enhances social engagement in three ways: (1) A messaging system that enables written communication, reducing the stress of face-to-face interactions. (2) Encouraging curiosity-driven discovery, easing the fear of direct engagement. (3) Enhancing users’ sense of presence through shared book interactions and library-based messaging. Ultimately, this study demonstrates how innovative library interactions—centered on books as social media—can create supportive environments that help individuals with SAD engage meaningfully with others.